2009
DOI: 10.1155/2009/121494
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Load in eCommerce Applications—Measurement and Effects on User Satisfaction

Abstract: Guidelines for designing usable interfaces recommend reducing short term memory load. Cognitive load, that is, working memory demands during problem solving, reasoning, or thinking, may affect users' general satisfaction and performance when completing complex tasks. Whereas in design guidelines numerous ways of reducing cognitive load in interactive systems are described, not many attempts have been made to measure cognitive load in Web applications, and few techniques exist. In this study participants' cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 41 publications
(63 reference statements)
2
35
0
Order By: Relevance
“…They found that the experimental system imposed no extra demands on user workload than the standard system. Schmutz et al [45] found significant correlations among mental demand, primary task completion time, and general user satisfaction in an experiment comparing four online bookstores.…”
Section: Workloadmentioning
confidence: 99%
“…They found that the experimental system imposed no extra demands on user workload than the standard system. Schmutz et al [45] found significant correlations among mental demand, primary task completion time, and general user satisfaction in an experiment comparing four online bookstores.…”
Section: Workloadmentioning
confidence: 99%
“…More research is needed on the application of the dualtask method in interactive IR studies to identify secondary tasks particularly suited for use in interactive IR experiments. Except for Dennis et al study (2002) using an auditory secondary task, subsequent studies have employed visual secondary tasks (e.g., Gwizdka, 2008;Schmutz, Heinz, Métrailler, & Opwis, 2009). As online searching now occurs on a variety of handheld devices, such as tablets and smart phones, haptic secondary tasks may also need to be developed.…”
mentioning
confidence: 99%
“…For small online businesses, measuring the relevance of search results can help understand whether the search facilities that they are using are efficient enough to provide the information that a customer needs [10]. For e-businesses, evaluating the capacity of the search engine is critical because users were found not willing to invest more time or more effort to improve their searching strategies [11]. They often settle on using simple keywords for searching and viewing only the first few pages of results by not going beyond 20 results.…”
Section: Relevance Of Search Resultsmentioning
confidence: 99%